2014
DOI: 10.1073/pnas.1314615111
|View full text |Cite
|
Sign up to set email alerts
|

Nonflammable perfluoropolyether-based electrolytes for lithium batteries

Abstract: The flammability of conventional alkyl carbonate electrolytes hinders the integration of large-scale lithium-ion batteries in transportation and grid storage applications. In this study, we have prepared a unique nonflammable electrolyte composed of low molecular weight perfluoropolyethers and bis(trifluoromethane)sulfonimide lithium salt. These electrolytes exhibit thermal stability beyond 200°C and a remarkably high transference number of at least 0.91 (more than double that of conventional electrolytes). Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
214
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(242 citation statements)
references
References 37 publications
22
214
0
Order By: Relevance
“…It is based on the measurement of conductivity by ac impedance, salt diffusion coefficient by restricted diffusion, steady-state current under dc polarization, and the thermodynamic factor using concentration cells. Our approach, based on concentrated solution theory, is very similar to that proposed by Ma et al 33 A majority of t + values reported in the literature [41][42][43][44][45][47][48][49]58,59,61 are based on the steady-state current method pioneered by Bruce and Vincent. 42,57 In a few cases [34][35][36][37] where the approach of Ma et al is used to determine t + , there is no attempt to relate t + values thus obtained with those that might be obtained using the steady-state current method.…”
Section: Discussionmentioning
confidence: 98%
“…It is based on the measurement of conductivity by ac impedance, salt diffusion coefficient by restricted diffusion, steady-state current under dc polarization, and the thermodynamic factor using concentration cells. Our approach, based on concentrated solution theory, is very similar to that proposed by Ma et al 33 A majority of t + values reported in the literature [41][42][43][44][45][47][48][49]58,59,61 are based on the steady-state current method pioneered by Bruce and Vincent. 42,57 In a few cases [34][35][36][37] where the approach of Ma et al is used to determine t + , there is no attempt to relate t + values thus obtained with those that might be obtained using the steady-state current method.…”
Section: Discussionmentioning
confidence: 98%
“…The exclusion of Li 2 S 8 from hybrid electrolyte may, at first, seem counterintuitive because of the presence of PFPE. Note, however, that solubility of lithium-containing salts in PFPE is driven by the fluorinated anions that are absent in lithium polysulfides (11). According to the data in Fig.…”
mentioning
confidence: 90%
“…In addition, we also studied a liquid electrolyte comprising a mixture of PFPE-diol and LiTFSI with r = 0.04 prepared using the method described in ref. 11. The compositions of all three electrolytes are given in Fig.…”
Section: Significancementioning
confidence: 99%
“…z E-mail: nbalsara@berkeley.edu transference number which has not yet been rigorously measured and is estimated to be between 0.1 and 0.2 based on preliminary data. 37 The numerical values reported in the previous sentence apply to high M n SEO copolymers. The electrochemical stability window of the electrolyte determine the potential of the battery.…”
mentioning
confidence: 99%